Mendelian randomization shows a causal effect of low vitamin D on multiple sclerosis risk. (October 2016) - Rhead, Brooke; Bäärnhielm, Maria; Gianfrancesco, Milena; Mok, Amanda; Shao, Xiaorong; Quach, Hong; Shen, Ling; Schaefer, Catherine; Link, Jenny; Gyllenberg, Alexandra; Hedström, Anna Karin; Olsson, Tomas; et al.
Abstract : Objective: We sought to estimate the causal effect of low serum 25(OH)D on multiple sclerosis (MS) susceptibility that is not confounded by environmental or lifestyle factors or subject to reverse causality. Methods: We conducted mendelian randomization (MR) analyses using an instrumental variable (IV) comprising 3 single nucleotide polymorphisms found to be associated with serum 25(OH)D levels at genome-wide significance. We analyzed the effect of the IV on MS risk and both age at onset and disease severity in 2 separate populations using logistic regression models that controlled for sex, year of birth, smoking, education, genetic ancestry, body mass index at age 18–20 years or in 20s, a weighted genetic risk score for 110 known MS-associated variants, and the presence of one or more HLA-DRB1*15:01 alleles. Results: Findings from MR analyses using the IV showed increasing levels of 25(OH)D are associated with a decreased risk of MS in both populations. In white, non-Hispanic members of Kaiser Permanente Northern California (1, 056 MS cases and 9, 015 controls), the odds ratio (OR) was 0.79 ( p = 0.04, 95% confidence interval (CI): 0.64–0.99). In members of a Swedish population from the Epidemiological Investigation of Multiple Sclerosis and Genes and Environment in Multiple Sclerosis MS case-control studies (6, 335 cases and 5, 762 controls), the OR was 0.86 ( p = 0.03, 95% CI: 0.76–0.98). A meta-analysis of the 2 populations gave a combined OR of 0.85 ( p = 0.003, 95% CI: 0.76–0.94). No association was observed for age at onset or disease severity. Conclusions: These results provide strong evidence that low serum 25(OH)D concentration is a cause of MS, independent of established risk factors.